The Symmetry of Lower Back Pain as a Potential Screening Factor for Serious Pathology: A Survey Study - Grzegorz Miękisiak (MDPI AG, 2021)
Background: Pain maps provide reliable information on pain location in various conditions. This study explored the feasibility of pain maps as a screening tools for serious underlying conditions. The pain symmetry was evaluated as the possible distinguishing feature. Methods: A Web-based survey on the correlation of pain-related disability and pain pattern was developed. Respondents with lower back pain were asked to mark the exact location of their pain over the pain chart. The symmetry index was calculated and used to divide subjects into two groups that were then compared in terms of the prevalence of red flags for serious pathologies, as well as the pain-related disability measured with COMI and ODI instruments. Results: Of the 4213 respondents who completed the survey, 1018 were included in the study. The pain related disability was greater in respondents with asymmetrical pain patterns, as shown with all instruments. The distribution of red flags was also dependent on pain symmetry. The history of weight loss (6.70 vs. 1.76 p < 0.001) and fever (4.91 vs. 2.14 p < 0.001) were more prevalent with symmetrical pain patterns, and the history of trauma was more frequent with asymmetrical pain (21.41 vs. 10.71 p < 0.001). Conclusions: It was shown that the symmetry of pain is correlated to the prevalence of red flags and pain-related disability.